Stakeholder perspectives on breeding strategy and choice of breeds for livestock development in Bangladesh - Jabbar, MA; Husain, SS; Islam, SMF; Amin, MR; Khandaker, MAMY; Bhuiyan, AKFH; Ali, SZ; Faruque, O (Bangladesh Journal of Animal Science, 2012)
In Bangladesh, a science based systematically organized pragmatic breeding policy has never been formulated and adopted. In breeding research and development projects, perspectives of stakeholders like researchers, extension agents and farmers on criteria for selection of breeds for adaptation in the country have not been adequately considered. In this paper, opinions of a sample of 128 university teachers, researchers and extension experts in the field of livestock and 196 farmers with at least one milking cow on criteria for selection of breeds and their relative weights and a number of other breed development issues are presented. The results show that there are significant differences among experts about the breeding objectives and strategies to be followed, on relative weights to be given on various traits for evaluation and selection of breeds and allocation of research resources on different species for breed development. Moreover, there are significant differences between experts and farmers about relative weights to be given for breed evaluation and selection, and on the extent of suitability of different available breeds for local adaptation. These results indicate that breeding research and development needs to be based on more such studies to facilitate serious debate and arrive at a consensus for adoption of long-term breeding policy. Key words: Stakeholder; Breeding strategy; Livestock; Breed DOI: http://dx.doi.org/10.3329/bjas.v39i1-2.9674 Bang. J. Anim. Sci. 2010, 39(1&2): 20-43